LATEGAN, H.A. Inventory of documents - LATEGAN, H.A. (ARCA, 2018)
Contains inter alia documents of the NP Women’s League, Kimberley
COVERAGE: 1929, 1938; 0.10 metres
Keywords: LATEGAN, H.A.; Inventories; Politicians; National Party